Food Consumption Pattern and Nutritional Status of Women Laborers from Coastal Areas of Karnataka - Archana Prabhat; Khyrunnisa Begum (Medsci Publications, 2012)
Introduction: Food consumption pattern fundamentally reflects nutritional well being of individuals and the meal pattern is defined by the culture and food availability. Objective: To investigate food consumption pattern and nutritional status of women laborers from coastal regions. Method: 120 women engaged in beedi (rolled tobacco leaves into a form of cigar) making, mason work, maids etc participated in the study. Standardized interview schedules were used to elicit information such as demography, food purchasing pattern and frequency of consuming different foods. Weight, height, MUAC and WHR were recorded using standard procedures and equipments. Results: Majority of the participants (79%) was daily wagers (DW) and 21% were on monthly payment (MP). Among the non vegetarian foods (82%), sea foods predominated and consumed daily. Fruit consumption was high (69.4%), curd and greens were obligatory items for lunch and dinner. Type of payment (DW/MP) and diet type (vegetarians/ non vegetarians) was found to exert influence on nutritional status of women, 68.5 and 72% of DW and MP had BMI in normal range, and 14.7% of DW had CED while 24% MP were overweight. Conversely, 22.5% of non vegetarian women had CED and 57.2% women had normal BMI against 81.8% of vegetarian women. Occurrence of obesity was less; however, 84% of all the participants regardless of payment and diet type had WHR > 0.91 indicating prevalence of central obesity. Conclusion: Nutritional status of women laborers was influenced by the type of payment; while central obesity was found to be a common feature.